Bibliometric analysis of rehabilitation in Alzheimer’s disease (2000–2023): trends, hotspots and prospects - Jun, Peng; Chengye, Hao; Hui, Wan (Frontiers in Aging Neuroscience, 2024)
BackgroundAlzheimer’s disease (AD) is a complex neurodegenerative disease that leads to insidious deterioration of brain functions and is considered the sixth leading cause of death in the world. Multiple studies have shown that rehabilitation therapy is becoming an important field of AD research in recent years.ObjectiveWe opted for bibliometric analysis to comprehensively summarize the advancements in the study of AD rehabilitation treatment, aiming to provide researchers with current trends and future research directions.MethodsAll articles and reviews pertaining to rehabilitation treatment in Alzheimer’s disease from 2000 to 2023 were downloaded through Web of Science Core Collection. The results were subjected to bibliometric analysis using Microsoft Excel (2019 version), CiteSpace (6.3 R1 Advanced) and VOSviewer 1.6.20.ResultsOverall, 1,284 publications were included. The number of publications was increasing yearly. The United States has published the most publications. University of Toronto has published the most papers of all institutions. NEUROPSYCHOLOGICAL REHABILITATION and ARCHIVES OF PHYSICAL MEDICINE AND REHABILITATION were the journals with the most studies and the most commonly cited, respectively. Clare L is the author with the highest productivity and co-citation. After analysis, the most common keywords are mild cognitive impairment, cognitive, impairment memory and executive function indicates that cognitive impairment is the main focus of research. Transcranial magnetic stimulation, cognitive rehabilitation, and physical activity/exercise are the hotspots of research at the present stage and are likely to continue.ConclusionDistinguishing non pharmacological treatments at different stages of development is a research hotspot in AD rehabilitation; Sports intervention, brain functional imaging techniques represented by brain functional connectivity, virtual reality, and quality of life are research directions that need attention.